Civilizational Islam: Promulgating the New Approach of Islam in Malaysia - Ahmad, Abdul Muati; Abdul Rahman, Saiful Nujaimi (2009)
The government of Malaysia has heralded Civilizational Islam (Islam Hadhari) to be adopted as a new approach towards developing a modern society in this country. The concept of Islam Hadhari was first mentioned during the 11 general election campaign sometimes in March 2004. Since then, Malaysians, Muslims and non-Muslims alike were expecting to observe more detail explanations of the new concept and how it could be translated into actions in the multi-religion society. The mainstream media has also allotted special columns and programs to extend the new concept even though at times not in detail and lack of continuity. Today, after more than two years since this concept has been conceived, what are the peoples' perceptions towards it? Do the people really made to understand the concept? To what extent has the media been used to disseminate the idea? This paper will discuss the analysis of the dissemination of the new concept through the media in Malaysia.